Combining time series and land cover data for analyzing spatio-temporal changes in mangrove forests: A case study of Qinglangang Nature Reserve, Hainan, China - Bin Zhu (Elsevier, 2021)
Mangrove forests have important social, ecological, and economic value in coastal ecosystems. However, they are one of the most vulnerable ecosystems in the world and are widely threatened due to their unique location along the land-sea interface. Thus, mangrove conservation based on scientific and effective monitoring methods is essential. In this study, a method for analyzing the spatio-temporal changes in mangrove forests was proposed in Qinglangang Nature Reserve, Hainan Province, China. This method combined multiple time series analysis (including Theil-Sen median trend analysis, Mann-Kendall test, and Hurst exponent) with land cover data from Landsat and Sentinel-1/2 to provide a clearer geographic explanation for changes in mangrove forests. The study showed that high-resolution data performs better than low-resolution data, optical indices are more ideal than SAR indices, and EVI is more advantageous than NDVI for mangrove time series analysis. The results revealed that mangroves in Qinglangang have experienced a severe degradation stage (1987–2003), a slow improvement stage (2003–2013), and a coexistence of improvement and degradation stage (2013–2020). In all stages, the main causes of mangrove degradation are anthropogenic factors, such as development of aquaculture ponds and building land, and natural factors caused by typhoons and sea-level rise. The anthropogenic factors have a broader and longer impact and should be a focus of future studies. The improvement in mangrove forests is due to habitat quality restoration and artificial planting, which is shown to be quite effective.